Prevalence of stroke cognition and health literacy in high-risk populations in Chengdu: a community-based cross-sectional study - Yue Wang; Chun-yu He; Wen-bo Chen; Xiao-qing Jiang; Yan Xie; Yan Xie; Yuan-mei Zhao; Ling Yuan (Frontiers in Neurology)
ObjectiveThe purpose of this study is to evaluate the awareness of stroke among high-risk populations in Chengdu and explore the factors contributing to it.MethodsA cross-sectional study was conducted involving 360 individuals identified as being at high risk for stroke, recruited from four community health service centers in Chengdu. Participants were first screened for stroke risk using a technical plan, followed by an assessment of socio-demographic factors and health education status through a pre-designed structured interview questionnaire. The Health Literacy Management Scale (HeLMS) was utilized to evaluate health literacy levels, while a stroke prevention and treatment knowledge questionnaire was used to assess stroke knowledge. Multiple linear stepwise regression analysis was employed to examine the relationship between stroke prevention knowledge and several independent variables.ResultsThe mean stroke prevention and treatment knowledge score were 21.95 ± 8.53, with the lowest score in the dimension of stroke management. The results of the regression analysis indicated that the dimensions of information acquisition ability (β = 0.330, p < 0.001), education level (β = 2.233, p < 0.001), communication interaction ability (β = 0.280, p < 0.001), Stroke health education experience (β = −0.117, p = 0.005), and hypertension diagnosis (β = −0.112, p = 0.007) can predict stroke prevention and treatment knowledge.ConclusionThis study investigated the knowledge level of stroke prevention and treatment and related influencing factors in high-risk population of stroke in Chengdu. Despite the general awareness of the importance of stroke prevention among high-risk individuals in Chengdu, there is a significant deficiency in their ability to identify stroke early and manage it correctly. There is an urgent need for more targeted and accessible health education initiatives.